Analysis of susceptibility profile of Pseudomonas spp. and prevalence of bacterial samples from the surfaces of dental consulting-rooms - R.C.L.R. Pietro; S. Kashima; A.M.F. Almeida; C.H.P.M. Silva; L.B. Rocha; J.M. Pádua; R.C.C. Lia (São Paulo State University (UNESP), 2005)
The aim of this research was to evaluate the susceptibility profile of Pseudomonas spp. and the prevalence of bacterial samples isolated from horizontal surfaces surrounding wash-basins used by dentists in several adjoined consulting-rooms, at points next to and at a distance from the basin, before and after surgical procedures. Our results showed a high percentage of Gram-positive cocci and Gram-negative bacilli; 34.66% were Staphylococcus spp. and 30.12% were nonfermentative Gram-negative bacilli among which Pseudomonas spp. (40.90%) was the commonest genus. Analysis of the susceptibility profile of Pseudomonas spp. isolates by determining the minimal inhibitory concentration (MIC) of 14 antibiotics showed a great variation among the strains and high rates of resistance to cefazolin, ceftazidime and aztreonan. Of the 14 antibiotics tested, 59.03% were found to be active against all the environmental isolates. Strains were resistant to aztreonan (62.82%), while susceptibility to third generation cephalosporins was variable.